AVALIAÇÃO DOS GAPS DE QUALIDADE SEGUNDO O MODELO SERVQUAL: UM ESTUDO DO SERVIÇO BANCÁRIO DE TRÊS PASSOS - Bencke, Osmar L. F.; Muhlbeier, Michele D.; Barriquello, Carlise; Vivian, Everton L.; Zamberlan, Luciano (Salão do Conhecimento, 2013)
Resumo